Two different Clostridium perfringens strains produce different levels of necrotic enteritis in broiler chickens. (19th August 2019) - Gharib-Naseri, K; Kheravii, S K; Keerqin, C; Morgan, N; Swick, R A; Choct, M; Wu, S-B
ABSTRACT: Subclinical necrotic enteritis (NE ) is primarily caused by the gram-positive bacterium, Clostridium perfringens ( Cp ). The trend towards removal of in-feed antimicrobials and subsequent increased emergence of infection in poultry has resulted in a wide interest in better understanding of the mechanism behind this disease. The virulence of NE, to a large extent, depends on the virulence of Cp strains. Thus, this study was to assess how 2 different strains of Cp affect performance and gut characteristics of broiler chickens. Ross 308 male broilers ( n = 468) were assigned to a 2 × 3 factorial arrangement of treatments with antibiotics (Salinomycin at 72 ppm and zinc bacitracin at 50 ppm −, or +) and challenge (non-challenge, Cp EHE-NE18, or Cp WER-NE36). Oral administration of Eimeria oocysts (day 9) followed by inoculation with 1 mL 10 8 CFU Cp strains (day 14 and 15) were used to induce NE. Broiler performance was analyzed at day 10, 24, and 35. On day 16, intestinal lesion score and intestinal pH were evaluated and samples of cecal content were analyzed for bacterial counts and short-chain fatty acid concentrations (SCFA ). Birds in both challenged groups showed higher feed conversion ratio (FCR ), lower weight gain ( P < 0.001), increased lesion scores in the jejunum ( P < 0.01), and reduced pH in the ileum and cecum ( P < 0.01), compared to the non-challenged birds. They also showed decreased numbers of Bacillus spp. ( P < 0.001), and Ruminococcus spp. ( P < 0.01) in the cecal content. On day 35, the NE36 challenged birds had a lower weight gain ( P < 0.001) and higher FCR ( P < 0.001) compared to the NE18 challenged birds. Interestingly, cecal Lactobacillus and lactate were increased by the NE challenge ( P < 0.001), and to a greater extent in birds challenged with NE36 compared to the NE18 strain ( P < 0.001). This study suggests that Cp strains varying in virulence produce different levels of disease in broiler chickens through modulating the gut environment, intestinal microbiota, and SCFA profile to different extents.